PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF TEACHING FOREIGN LANGUAGES - Shodiyarova , Mohira (SAMBHRAM XABARNOMASI, 2024)
Annotation. Pedagogical conditions are conditions that ensure the effectiveness of the pedagogical system and the success of the pedagogical process. Pedagogical conditions mean the possibilities, methods, organizational forms of teaching content and the material possibilities of its implementation. Annotatsiya. Pedagogik shart- sharoitlar pedagogik tizim faoliyatining samaradorligini, pedagogik jarayonning muvaffaqiyatini ta’minlaydigan holatlardir. Pedagogik shart- sharoitlar deganda o’qitish mazmuni imkoniyatlari, usullari,tashkiliy shakllari va uni amalga oshirishning moddiy imkoniyatlari majmui tushuniladi. Аннотация. Педагогические условия–это условия, обеспечивающие эффективность педагогической системы и успешность педагогического процесса. Педагогические условия подразумевают совокупность возможностей, методов, организационных форм и материальных возможностей ее реализации.